2009
DOI: 10.1371/journal.pbio.1000155
|View full text |Cite
|
Sign up to set email alerts
|

CFTR Delivery to 25% of Surface Epithelial Cells Restores Normal Rates of Mucus Transport to Human Cystic Fibrosis Airway Epithelium

Abstract: Delivering CFTR to ciliated cells of cystic fibrosis (CF) patients fully restores ion and fluid transport to the lumenal surface of airway epithelium and returns mucus transport rates to those of non-CF airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
148
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(159 citation statements)
references
References 57 publications
8
148
3
Order By: Relevance
“…2B). These data are consistent with results from human airway epithelia expressing either endogenous levels of CFTR or overexpressing CFTR (10)(11)(12)(13)(14). However, as the percentage of WT cells increased, Airway epithelia were generated with varying ratios of CFTR ΔF508/ΔF508 and CFTR +/+ cells.…”
Section: Hcosupporting
confidence: 87%
See 3 more Smart Citations
“…2B). These data are consistent with results from human airway epithelia expressing either endogenous levels of CFTR or overexpressing CFTR (10)(11)(12)(13)(14). However, as the percentage of WT cells increased, Airway epithelia were generated with varying ratios of CFTR ΔF508/ΔF508 and CFTR +/+ cells.…”
Section: Hcosupporting
confidence: 87%
“…In contrast, a different study reported that CFTR expression in all of the cells reduced ΔIsc (amiloride) , but there was no relationship to vector dose (44). Between those extremes, one study reported that, as the percentage of transduced cells increased (∼60% was the highest percentage tested), ΔIsc (amiloride) progressively decreased (12). Another study reported variable effects of CFTR expression on basal transepithelial voltage in CF xenografts (11).…”
Section: Hcomentioning
confidence: 99%
See 2 more Smart Citations
“…The osmotic potential exerted by CF mucus (.8% solids), but not healthy mucus (;2% solids), was demonstrated to be sufficient to dehydrate the PCL and collapse cilia (52), and to restrict mobility of bacteria and foster formation of bacterial biofilm precursor macrocolonies (53). Restoration of CFTR expression in CF primary epithelial cells by viral transduction significantly increases ASL depth, ciliary beat frequency, and mucus transport, supporting the idea that loss of CFTR function mediates ASL dehydration (54). Therefore, the bulk of available evidence links reduced ASL volume to increased propensity for infection, with reduced CFTR ion transport leading to reduced mucin hydration in the mucus layer followed by PCL dehydration, ciliary collapse, mucostasis, and bacterial colonization.…”
mentioning
confidence: 66%